Genetic diversity in some Aegilops species in Jordan revealed using RAPD - Migdadi, H.M.=700 1 Majid Tell, A.; Masoud, S.
(En, Fr, Es)
ilus., 12 ref.
Keywords: AEGILOPS; VARIACION GENETICA; TECNICAS ANALITICAS; JODANIA; TRIGO